Water-based high-barrier ink and preparation method thereof

By combining modified polyvinyl alcohol with acrylic resin emulsion, nanocomposite materials, and bio-based plasticizers, the problem of poor barrier properties of traditional water-based inks has been solved, resulting in water-based inks with high barrier properties, excellent printability, and environmental friendliness, suitable for high-end packaging.

CN120966309APending Publication Date: 2025-11-18CHENGDU XINJIN TUOZHAN PRINTING INK

Patent Information

Application Number
CN202511296735.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Traditional water-based inks have weak barrier properties, making it difficult to meet the high barrier performance requirements of food, pharmaceutical and other packaging materials. Existing technologies also suffer from poor dispersibility of nanomaterials and poor compatibility with water-based resins.

Method used

By combining modified polyvinyl alcohol with acrylic resin emulsion, adding nanocomposite materials and bio-based plasticizers, and precisely controlling the component ratio and specific feeding sequence, the nanoparticles are uniformly dispersed to form an ink with high barrier properties.

Benefits of technology

It significantly reduces oxygen and water vapor permeability, improves printability and flexibility, meets the needs of high-end packaging for preservation, moisture protection, and odor prevention, and is both environmentally friendly and multifunctional.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses water-based high-barrier ink and a preparation method thereof, and relates to the technical field of ink. The water-based high-barrier printing ink is prepared from the following components: polyvinyl alcohol emulsion, acrylic resin emulsion, a nano composite material, a bio-based plasticizer, a dispersing agent, a wetting agent, a defoaming agent, a flatting agent and water. The preparation method comprises the following steps: preparation of a polyvinyl alcohol emulsion: dissolving polyvinyl alcohol in water, and adjusting the pH value to 2-4; adding a cross-linking agent for complete reaction; adding an emulsifier, stirring and emulsifying to obtain a polyvinyl alcohol emulsion; the raw materials are mixed and react according to the component proportion of the water-based high-barrier ink to obtain the water-based high-barrier ink. The high-barrier-property environment-friendly packaging film has high barrier property and excellent printability, meanwhile, the environment-friendly property is achieved to the maximum extent, and the high-barrier-property environment-friendly packaging film has the additional advantages of being good in flexibility, stability and the like and meets the urgent requirements of the high-end and environment-friendly packaging market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ink technology, specifically to a water-based high-barrier ink and its preparation method. Background Technology

[0002] With increasingly stringent environmental regulations and consumers' growing demand for safety, water-based inks are gradually replacing traditional solvent-based inks, becoming the mainstream choice in the printing industry for high-end packaging of food, pharmaceuticals, and electronic devices. However, traditional water-based inks have an oxygen transmission rate (OTR) of 15~20 cc / m²·day and a water vapor transmission rate (WVTR) of 8~12 g / m²·day. Furthermore, traditional water-based inks exhibit oil penetration within 24 hours, making it difficult to meet the high barrier performance requirements of food and pharmaceutical packaging materials.

[0003] The main reasons for the weak barrier properties of traditional water-based inks are poor film density, and the use of water as a dispersion medium leading to reduced resin molecular chain entanglement and weak interfacial bonding. Existing technologies for improving the barrier properties of water-based inks mainly include: adding inorganic nanomaterials, such as nano-silica and nano-alumina, but these suffer from poor dispersibility and easy agglomeration, affecting ink performance; and adding organic barrier agents, such as polyvinyl alcohol and polyvinylidene chloride, but these have problems such as poor compatibility with water-based resins and affecting ink printability.

[0004] Currently, there is no water-based ink that combines high barrier properties, excellent printability, environmental friendliness, and multifunctionality. Summary of the Invention

[0005] The purpose of this invention is to provide a water-based high-barrier ink and its preparation method, which improves the problems of poor barrier performance and poor printability of existing water-based inks, and combines high barrier performance, excellent printability, environmental friendliness and multifunctionality.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0007] A water-based high-barrier ink, comprising the following components by weight percentage:

[0008] Polyvinyl alcohol emulsion 20-40%, acrylic resin emulsion 10-20%, nanocomposite material 5-15%, bio-based plasticizer 3-8%, dispersant 1-3%, wetting agent 0.2-1%, defoamer 0.1-0.5%, leveling agent 0.1-0.5%, balance water;

[0009] The polyvinyl alcohol emulsion contains 18-23% polyvinyl alcohol by mass, and the acrylic resin emulsion contains 47-52% acrylic resin by mass.

[0010] Polyvinyl alcohol (PVA) emulsions are used as the main film-forming agent. PVA has a relative molecular mass range of 60,000-75,000, but pure PVA films are typically brittle, lack flexibility, have poor water resistance, and poor printability. High-solids acrylic resin emulsions, on the other hand, offer excellent film-forming properties, flexibility, adhesion, gloss, water resistance, and good printability. This invention modifies PVA and then combines it with acrylic resin emulsions. By precisely controlling the ratio of the two (PVA as the main component and acrylic as the auxiliary component), the high barrier properties of PVA and the excellent comprehensive properties of acrylic resin are combined. This significantly improves the printability, flexibility, and water resistance of the ink while maintaining high barrier properties. Simultaneously, nanocomposite materials with extremely large specific surface area and special physical barrier effects are added. The nanoparticles are uniformly dispersed in the polymer matrix, significantly extending the permeation path of gases and water vapor, thereby further enhancing the barrier performance on top of the original polyvinyl alcohol barrier layer. 3-8% bio-based plasticizers are used to improve the flexibility and anti-brittleness of the polyvinyl alcohol film, making it less prone to cracking during printing and subsequent processing. The selection of bio-based plasticizers enhances the environmental friendliness of the formulation and reduces reliance on traditional petroleum-based phthalate plasticizers.

[0011] Both polyvinyl alcohol emulsion and acrylic resin emulsion have high solid content, especially acrylic emulsion, which helps reduce water usage, improves drying speed, and enhances the performance of the final coating. Sufficient dispersant (1-3%) is crucial for stabilizing nanoparticles. Appropriate addition of wetting agents, defoamers, and leveling agents ensures good ink spreadability, bubble-free operation, and smooth leveling during printing. Using water as the primary solvent fundamentally guarantees low VOCs and environmental friendliness.

[0012] This invention combines the inherent excellent oxygen barrier properties of polyvinyl alcohol with the physical barrier effect of nanocomposite materials, significantly reducing the permeability of oxygen (O2) and water vapor (H2O). It also exhibits good barrier effects against oils and aromas, meeting the stringent requirements of high-end packaging, especially for food, pharmaceuticals, and electronic products, which demand long-term preservation, moisture control, aroma retention, and prevention of odor intrusion. The addition of acrylic resin and the application of bio-based plasticizers greatly improve the ink's leveling properties, film-forming properties, flexibility, and adhesion to substrates (such as plastic films and paper). The combination of bio-based plasticizers and acrylic resins gives the ink film excellent flexibility, making it suitable for flexible packaging materials requiring bending and folding. The acrylic resin and nanocomposite materials synergistically improve the inherent water resistance deficiency of polyvinyl alcohol.

[0013] In this invention, the dispersant can be sodium polyacrylate or sodium hexametaphosphate; the wetting agent can be acetylenic diol wetting agent; the defoamer can be silicone defoamer or mineral oil defoamer; and the leveling agent can be silicone leveling agent or fluorocarbon leveling agent.

[0014] In addition, the water-based high-barrier formulation of the present invention can also add 10-30 wt% of pigments, such as titanium dioxide, carbon black or phthalocyanine blue, to meet different color requirements; antibacterial agents can also be added, with the mass ratio of antibacterial agent to polyvinyl alcohol being 0.3-2:10, such as nano silver or zinc oxide, to give the ink antibacterial properties; anti-counterfeiting materials, such as thermochromic materials or photochromic materials, can also be added to give the ink anti-counterfeiting functions.

[0015] Furthermore, the nanocomposite material is a nanomaterial modified by a silane coupling agent, and the nanomaterial includes nano-clay or nano-silica.

[0016] Furthermore, the bio-based plasticizer includes citrate esters or epoxidized soybean oil.

[0017] A preparation method suitable for preparing the aforementioned water-based high-barrier ink includes the following steps:

[0018] Preparation of S100 polyvinyl alcohol emulsion: Dissolve polyvinyl alcohol in water and adjust the pH to 2-4; add a crosslinking agent and react completely; add an emulsifier and stir to emulsify to obtain a polyvinyl alcohol emulsion;

[0019] S200, Preparation of water-based high-barrier ink: The raw materials are mixed and reacted according to the component ratio of the water-based high-barrier ink as described in any one of claims 1 to 3 to obtain the water-based high-barrier ink.

[0020] This invention involves a crosslinking reaction during the polyvinyl alcohol (PVA) dissolution stage. This crosslinking significantly improves the performance of PVA emulsions: the crosslinked network reduces the number of hydrophilic hydroxyl groups in PVA, greatly improving the water resistance of the emulsion film and overcoming the fatal weakness of poor water resistance in pure PVA; the crosslinked structure enhances the tensile strength, abrasion resistance, and tear resistance of the film; the crosslinking points restrict molecular chain movement, improving the film's heat resistance; and moderate crosslinking may contribute to the formation of more stable emulsion particles. Precisely controlled chemical crosslinking modification during the dissolution stage resolves the contradiction between PVA barrier properties and water resistance / mechanical properties, providing a foundation for the high barrier properties and comprehensive performance of inks.

[0021] Further, in step S100, the crosslinking agent includes glutaraldehyde or glyoxal, and the molar ratio of the crosslinking agent to the polyvinyl alcohol monomer unit is 1:9~11.

[0022] The preparation method of this invention involves directly performing a crosslinking reaction in a dissolved polyvinyl alcohol aqueous solution, followed by emulsification. Glutaraldehyde or glyoxal is selected as the crosslinking agent, and the acetalization reaction is carried out under acidic conditions (pH 2-4). The molar ratio of glutaraldehyde or glyoxal to PVA monomer units is controlled at 1:9-11. This aims to ensure the degree of crosslinking (improving water resistance and strength) while considering reaction efficiency and the aqueous solution environment, ensuring that the crosslinking agent molecules react with the polyvinyl alcohol chains to form a suitable crosslinked network.

[0023] Further, in step S100, the emulsifier includes sodium dodecyl sulfate or OP-10, and the emulsifier accounts for 0.5~1% of the total mass of the monomers.

[0024] Further, step S100 specifically includes: dissolving polyvinyl alcohol in water, heating to 80~90℃, stirring until completely dissolved, adjusting the pH to 2~4; adding a crosslinking agent to react 1~2; cooling to 50~60℃, adding an emulsifier, stirring to emulsify, and obtaining a polyvinyl alcohol emulsion.

[0025] In an acidic environment, the crosslinking reaction is carried out at a higher temperature (80-90℃ after dissolution), which is beneficial to the reaction rate. After the reaction is completed, the temperature is lowered to 50-60℃ before adding the emulsifier for emulsification. This avoids the possible decomposition or failure of the emulsifier under high temperature and acidic conditions. Emulsification at a moderate temperature of 50-60℃ is conducive to the formation of a more stable emulsion with more uniform particle size. Lowering the temperature before adding the emulsifier ensures that the crosslinking reaction has been basically completed and avoids the emulsifier interfering with the crosslinking reaction.

[0026] Furthermore, in step S200, the preparation of the water-based high-barrier ink includes the following steps:

[0027] Step 1: Add water, dispersant, wetting agent, defoamer, and leveling agent to the mixing tank and stir until homogeneous;

[0028] Step 2: Add the nanocomposite material and disperse it at high speed until the fineness is ≤10μm;

[0029] Step 3: Add modified polyvinyl alcohol emulsion and acrylic resin emulsion, and stir until homogeneous;

[0030] Step 4: Filter to obtain water-based high-barrier ink.

[0031] The preparation of water-based high-barrier inks follows a mixing sequence of first, aqueous phase of additives, then nanomaterials, and finally resin emulsion. First, dispersants, wetting agents, and other additives are thoroughly mixed in water to create a favorable dispersion environment. Then, nanocomposite materials are added under high shear force (high-speed dispersion) to ensure that the nanoparticles are fully deagglomerated, wetted, and stably dispersed in the system, thereby achieving high barrier performance. A dispersion fineness ≤10μm ensures effective dispersion and final printing quality.

[0032] After the nanomaterials are fully dispersed, the modified polyvinyl alcohol emulsion and acrylic emulsion are added. If the resin is added first, its polymer chains may encapsulate the nanoparticles, hindering the action of the dispersant, leading to uneven dispersion and easy aggregation of nanoparticles, which seriously affects the barrier effect and ink stability. Adding the emulsion last avoids the risk of demulsification caused by prolonged high shear force acting on the emulsion particles.

[0033] The specific feeding sequence, which is specially optimized for the coexistence system of high-content nanomaterials and resin emulsions in this formulation, scientifically solves the potential contradiction between nano-dispersion and resin emulsion stability. This is a key process step to ensure that the enhanced barrier properties of nanocomposites are achieved.

[0034] The specific feeding sequence and high-speed dispersion process ensure the uniform dispersion and stability of the nanocomposite material in the ink system to the greatest extent, giving full play to its "maze effect" and significantly improving its barrier properties (oxygen, water vapor, grease). Achieving a fineness of ≤10μm ensures the ink's printability (leveling, gloss, dot reproduction) and storage stability.

[0035] Through process control, the advantages of each component (modified polyvinyl alcohol, acrylic resin, nanomaterials, and additives) are effectively integrated, and the high barrier properties, excellent printability, flexibility, and water resistance of the formulation design are synergistically achieved. The process itself helps to maintain the activity of each component and reduce performance loss.

[0036] In the preparation process of this invention, reasonable process steps, such as emulsification after cooling in S100, subsequent addition of emulsion in S200, and parameter control, maximize the storage and application stability of the intermediate product (polyvinyl alcohol emulsion) and the final ink product, and reduce phenomena such as sedimentation, flocculation, water separation, and demulsification.

[0037] Pigments, antibacterial agents, and anti-counterfeiting materials can be added in step 2.

[0038] Furthermore, the preparation method of the nanocomposite material includes the following: dispersing the nanomaterial in water at a solid-liquid ratio of 1:1.8~2.1, adding a silane coupling agent, and reacting at 60~80℃ for 2~3 hours; filtering, washing, and drying to obtain the surface-modified nanocomposite material.

[0039] The solid-liquid ratio (1:1.8~2.1) ensures that the nanomaterials form a sufficiently high concentration slurry in water, which is beneficial to the effective adsorption and reaction of the subsequent coupling agent. At the same time, the viscosity is moderate, which ensures good stirring and mixing effect, and will not cause ineffective dispersion or uneven reaction due to excessive concentration.

[0040] Furthermore, the molar ratio of nanomaterials to silane coupling agent is 18~21:1.

[0041] The molar ratio (nanomaterial:silane coupling agent = 18~21:1), significantly lower than conventional silane coupling agent dosage, forms a dense monolayer on the nanomaterial surface, achieving monolayer grafting while maximally suppressing harmful self-polymerization reactions. The organic functional groups grafted onto the nanoparticle surface can physically entangle or chemically bond with polymers (such as the carboxyl / hydroxyl groups of acrylic resins and polyvinyl alcohol), significantly improving interfacial adhesion and avoiding stress concentration and performance degradation caused by weak interfaces. This is key to fully leveraging the reinforcing and barrier effects of nanomaterials. Uniform dispersion and strong interfacial bonding ensure that nanoparticles effectively extend the gas / water vapor permeation path, significantly improving the barrier properties of the ink coating (oxygen, water vapor, grease). Simultaneously, it also more effectively improves the mechanical properties of the coating (such as strength and abrasion resistance). Using water as the primary medium for modification avoids the use of organic solvents, meeting the overall environmental requirements of the ink.

[0042] Silane coupling agents can be selected from γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792), and γ-(methacryloyloxy)propyltrimethoxysilane (KH-570), etc.

[0043] γ-aminopropyltriethoxysilane (KH-550) is preferred.

[0044] The amino group (-NH2) of KH-550 preferentially forms ionic / amide bonds with the carboxyl groups (-COOH) of the acrylic resin in the ink, which is more rapid than the ring-opening reaction of the epoxy group in KH-560, significantly improving the interfacial bonding between nanomaterials and resin. The aminosilane-modified nanoparticles exhibit enhanced hydrophobicity, better meeting the anti-bleeding requirements of high-barrier inks. The amino groups protonate (-NH3) under acidic conditions. + The negatively charged nano-clay is electrostatically attracted to the nano-clay, enhancing its dispersion stability.

[0045] Compared with the prior art, the beneficial effects of the present invention are:

[0046] 1. This invention combines polyvinyl alcohol emulsion and acrylic resin emulsion, and synergistically utilizes nanocomposite materials and bio-based plasticizers. Through precise proportioning of each component, a multi-objective optimized balance is achieved. This invention also possesses high barrier properties: oxygen permeability less than 4.2 cc / m²·day and water vapor permeability less than 2.4 g / m²·day, and excellent printability: fineness ≤5μm, adhesion strength ≥97%, suitable for high-speed printing. Simultaneously, it maximizes environmental friendliness and possesses additional advantages such as good flexibility and stability, meeting the urgent needs of the high-end, environmentally friendly packaging market.

[0047] 2. The equipment used in this invention are all conventional chemical equipment. The process steps are clear, the parameters are well defined, and it has good operability and repeatability, making it suitable for industrial production. The entire preparation process uses water as a medium, without harsh conditions such as high temperature and high pressure, and without the volatilization of large amounts of organic solvents, which meets environmental protection requirements. Precise process control helps to reduce raw material waste and energy consumption.

[0048] OP-10 is a nonionic surfactant with the chemical name alkylphenol polyoxyethylene ether-10. Detailed Implementation

[0049] Example 1

[0050] The preparation method of the nanocomposite material includes the following: 2 mol of nano-silica is dispersed in 240 mL of water at a solid-liquid ratio of 1:2, 0.1 mol of KH550 is added, and the mixture is reacted at 70 °C for 2.5 hours; the mixture is then filtered, washed, and dried to obtain the surface-modified nanocomposite material.

[0051] Example 2

[0052] The preparation method of the nanocomposite material includes the following: 1.8 mol of nano clay is dispersed in 194.4 mL of water at a solid-liquid ratio of 1:1.8, 0.1 mol of KH550 is added, and the mixture is reacted at 60 °C for 2 hours; the mixture is then filtered, washed, and dried to obtain the surface-modified nanocomposite material.

[0053] Example 3

[0054] The preparation method of the nanocomposite material includes the following: 2.1 mol of silica is dispersed in 264.6 mL of water at a solid-liquid ratio of 1:2.1, 0.1 mol of KH550 is added, and the mixture is reacted at 80 °C for 3 hours; the mixture is then filtered, washed, and dried to obtain the surface-modified nanocomposite material.

[0055] The performance parameters of the nanocomposite materials prepared using Examples 1-3 are shown in Table 1.

[0056] Table 1 Performance parameters of the nanocomposite materials prepared using Examples 1-3

[0057] performance Example 1 (SiO2) Example 2 (Clay) Example 3 (SiO2) Dispersion Fineness ≤50 nm The interlayer spacing was increased by 1.2 times. Fineness ≤60 nm Grafting rate 78% 82% 75% Ink oxygen barrier Up 40% Up 35% Up 38% Storage stability No settlement for 6 months >4 months without gel No settlement for 5 months

[0058] Note: Grafting rate was determined by TGA loss method; oxygen barrier properties were tested according to GB / T 1038 standard.

[0059] As shown in Table 1, in Examples 1 and 3, due to the use of nano-silica with a large specific surface area and easy aggregation, a solid-liquid ratio of 1:2~2.1 was used, and high water content ensured dispersibility. In Example 1, the fineness was ≤50nm, the grafting rate reached 78%, achieving single-layer coverage grafting, and the oxygen barrier properties of the ink were improved by 40% compared to the unmodified version, with no sedimentation for more than 6 months. In Example 1, the fineness was ≤50nm, the grafting rate reached 78%, achieving single-layer coverage grafting, and the oxygen barrier properties of the ink were improved by 40% compared to the unmodified version, with no sedimentation for more than 6 months.

[0060] In Example 3, the fineness is ≤50nm, and the grafting rate can reach 78%, achieving single-layer coverage grafting. The oxygen barrier properties of the ink are improved by 40% compared to the unmodified version, and there is no sedimentation for more than 6 months. In Example 1, the fineness is ≤60nm, and the grafting rate can reach 75%, achieving single-layer coverage grafting. The oxygen barrier properties of the ink are improved by 38% compared to the unmodified version, and there is no sedimentation for more than 5 months. Reacting at 80℃ for 3 hours may lead to a small amount of self-polymerization reaction; therefore, the preferred modification conditions for nano-silica are those of Example 1.

[0061] In Example 2, nano-clay was used. Due to the layered structure of the clay absorbing water and swelling, a high water content may lead to a sharp increase in viscosity, so the concentration needs to be controlled, with a solid-liquid ratio of 1:1.8. After modification, the spacing between clay layers increased to 1.2 times the original, and the grafting rate was 82%, which is better than Examples 1 and 3. The oxygen barrier properties of the ink were improved by 35% compared with the unmodified version, and there was no gelation after storage for more than 4 months.

[0062] Example 4

[0063] A water-based high-barrier ink comprises the following components:

[0064] Polyvinyl alcohol emulsion 30g, acrylic resin emulsion 15g, nanocomposite material (prepared by the method in Example 1) 10g, citrate ester 5g, sodium polyacrylate 2g, acetylenol wetting agent (TEGO-510) 0.5g, organosilicon waterborne defoamer (BYK-024) 0.3g, polyether modified polydimethylsiloxane (BYK-333) 0.3g, water 36.9g;

[0065] The polyvinyl alcohol emulsion contains 20% polyvinyl alcohol by mass, and the acrylic resin emulsion contains 50% acrylic resin by mass.

[0066] A preparation method suitable for preparing the aforementioned water-based high-barrier ink includes the following steps:

[0067] Preparation of S100 polyvinyl alcohol emulsion: Dissolve 6g of polyvinyl alcohol in 24g of water, heat to 85℃, stir until completely dissolved, and adjust the pH to 3; add 0.3g of glutaraldehyde and react for 1.5h; cool to 55℃, add 0.05g of sodium dodecyl sulfate emulsifier, stir and emulsify to obtain polyvinyl alcohol emulsion;

[0068] The preparation of S200 water-based high-barrier ink includes the following steps:

[0069] Step 1: Add water, dispersant, wetting agent, defoamer, and leveling agent to the mixing tank and stir until homogeneous;

[0070] Step 2: Add the nanocomposite material and disperse it at high speed until the fineness is ≤10μm;

[0071] Step 3: Add modified polyvinyl alcohol emulsion and acrylic resin emulsion, and stir until homogeneous;

[0072] Step 4: Filter through a 200-mesh sieve to obtain water-based high-barrier ink.

[0073] The molar ratio of glutaraldehyde to PVA monomer units is 1:10.

[0074] Sodium dodecyl sulfate accounts for 0.8% of the total mass of the monomers.

[0075] Example 5

[0076] A water-based high-barrier ink comprises the following components:

[0077] 40g polyvinyl alcohol emulsion, 20g acrylic resin emulsion, 15g nanocomposite material (prepared by the method in Example 1), 8g citrate, 3g sodium hexametaphosphate, 1g acetylenol wetting agent (TEGO-510), 0.5g organosilicon waterborne defoamer (BYK-024), 0.5g polyether-modified polydimethylsiloxane (BYK-333), and 12g water;

[0078] The polyvinyl alcohol emulsion contains 23% polyvinyl alcohol by mass, and the acrylic resin emulsion contains 52% acrylic resin by mass.

[0079] A preparation method suitable for preparing the aforementioned water-based high-barrier ink includes the following steps:

[0080] Preparation of S100 polyvinyl alcohol emulsion: Dissolve 9.2g of polyvinyl alcohol in 30.8g of water, heat to 90℃, stir until completely dissolved, and adjust the pH to 4; add 0.2g of glyoxal and react for 2h; cool to 60℃, add 0.1g of OP-10 emulsifier, stir and emulsify to obtain polyvinyl alcohol emulsion;

[0081] The preparation of S200 water-based high-barrier ink includes the following steps:

[0082] Step 1: Add water, dispersant, wetting agent, defoamer, and leveling agent to the mixing tank and stir until homogeneous;

[0083] Step 2: Add the nanocomposite material and disperse it at high speed until the fineness is ≤10μm;

[0084] Step 3: Add modified polyvinyl alcohol emulsion and acrylic resin emulsion, and stir until homogeneous;

[0085] Step 4: Filter through a 200-mesh sieve to obtain water-based high-barrier ink.

[0086] The molar ratio of glyoxal to polyvinyl alcohol is 1:11.

[0087] Sodium dodecyl sulfate accounts for 1% of the total mass of the monomers.

[0088] Example 6

[0089] A water-based high-barrier ink comprises the following components:

[0090] 20g polyvinyl alcohol emulsion, 10g acrylic resin emulsion, 5g nanocomposite material (prepared by the method in Example 3), 3g epoxidized soybean oil, 1g sodium polyacrylate, 0.2g acetylenol wetting agent (TEGO-510), 0.1g organosilicon waterborne defoamer (BYK-024), 0.1g polyether modified polydimethylsiloxane (BYK-333), and 60.6g water;

[0091] The polyvinyl alcohol emulsion contains 18% polyvinyl alcohol by mass, and the acrylic resin emulsion contains 47% acrylic resin by mass.

[0092] A preparation method suitable for preparing the aforementioned water-based high-barrier ink includes the following steps:

[0093] Preparation of S100 polyvinyl alcohol emulsion: Dissolve 3.6g of polyvinyl alcohol in 16.4g of water, heat to 80℃, stir until completely dissolved, and adjust the pH to 2; add 0.15g of glutaraldehyde and react for 1h; cool to 50℃, add 0.02g of sodium dodecyl sulfate, stir and emulsify to obtain polyvinyl alcohol emulsion;

[0094] The preparation of S200 water-based high-barrier ink includes the following steps:

[0095] Step 1: Add water, dispersant, wetting agent, defoamer, and leveling agent to the mixing tank and stir until homogeneous;

[0096] Step 2: Add the nanocomposite material and disperse it at high speed until the fineness is ≤10μm;

[0097] Step 3: Add modified polyvinyl alcohol emulsion and acrylic resin emulsion, and stir until homogeneous;

[0098] Step 4: Filter through a 200-mesh sieve to obtain water-based high-barrier ink.

[0099] The molar ratio of glutaraldehyde to polyvinyl alcohol is 1:9.

[0100] Sodium dodecyl sulfate accounts for 0.5% of the total mass of the monomers.

[0101] Example 7

[0102] A water-based high-barrier ink comprises the following components:

[0103] Polyvinyl alcohol emulsion 30g, acrylic resin emulsion 15g, nanocomposite material (prepared by the method in Example 1) 10g, citrate ester 5g, sodium polyacrylate 2g, acetylenol wetting agent (TEGO-510) 1g, organosilicon waterborne defoamer (BYK-024) 0.3g, polyether modified polydimethylsiloxane (BYK-333) 0.3g, water 36.4g; titanium dioxide 15g; nano silver 3g.

[0104] The polyvinyl alcohol emulsion contains 20% polyvinyl alcohol by mass, and the acrylic resin emulsion contains 50% acrylic resin by mass.

[0105] A preparation method suitable for preparing the aforementioned water-based high-barrier ink includes the following steps:

[0106] Preparation of S100 polyvinyl alcohol emulsion: Polyvinyl alcohol is dissolved in water, heated to 85°C, stirred until completely dissolved, and the pH is adjusted to 3; a crosslinking agent is added and reacted for 1.5 h; the temperature is lowered to 55°C, 0.1 g of sodium dodecyl sulfate is added, and the mixture is stirred to emulsify, thus obtaining a polyvinyl alcohol emulsion;

[0107] The preparation of S200 water-based high-barrier ink includes the following steps:

[0108] Step 1: Add water, dispersant, wetting agent, defoamer, and leveling agent to the mixing tank and stir until homogeneous;

[0109] Step 2: Add titanium dioxide, nanocomposite materials and nano silver, and disperse at high speed until the fineness is ≤10μm;

[0110] Step 3: Add modified polyvinyl alcohol emulsion and acrylic resin emulsion, and stir until homogeneous;

[0111] Step 4: Filter through a 200-mesh sieve to obtain water-based high-barrier ink.

[0112] The molar ratio of glutaraldehyde to polyvinyl alcohol is 1:10.

[0113] Sodium dodecyl sulfate accounts for 0.8% of the total mass of the monomers.

[0114] Comparative Example 1

[0115] A water-based ink, comprising the following components:

[0116] The composition includes 35g acrylic resin emulsion, 5g dibutyl phthalate, 2g sodium polyacrylate, 1g acetylenol wetting agent (TEGO-510), 0.3g silicone waterborne defoamer (BYK-024), 0.3g polyether-modified polydimethylsiloxane (BYK-333), and 36.4g water; the mass fraction of acrylic resin in the acrylic resin emulsion is 50%.

[0117] Preparation method: Mix the above raw material components evenly, filter, and the water-based ink is obtained.

[0118] Comparative Example 2

[0119] A water-based ink, comprising the following components:

[0120] 30g of unmodified polyvinyl alcohol emulsion, 15g of acrylic resin emulsion, 15g of unmodified nano silica, 2g of sodium polyacrylate, 1g of acetylenol wetting agent (TEGO-510), 0.3g of organosilicon waterborne defoamer (BYK-024), 0.3g of polyether-modified polydimethylsiloxane (BYK-333), and 36.4g of water;

[0121] The polyvinyl alcohol emulsion contains 20% polyvinyl alcohol by mass, and the acrylic resin emulsion contains 50% acrylic resin by mass.

[0122] A method for preparing water-based ink includes the following steps:

[0123] Step 1: Add water, dispersant, wetting agent, defoamer, and leveling agent to the mixing tank and stir until homogeneous;

[0124] Step 2: Add nanocomposite material, polyvinyl alcohol emulsion and acrylic resin emulsion, and disperse at high speed until the fineness is ≤10μm;

[0125] Step 3: Filter through a 200-mesh sieve to obtain water-based ink.

[0126] Comparative Example 3

[0127] A solvent-based ink comprises the following components:

[0128] 30g polyurethane resin liquid, 15g chlorinated vinyl acetate resin liquid, 1g dispersant 24000 (Lubrizol), 10g nano calcium carbonate, 44g ethyl acetate;

[0129] Preparation method: Mix the above raw material components evenly, filter, and the solvent-based ink is obtained.

[0130] The performance parameters of the inks prepared in Examples 4-6 and Comparative Examples 1-3 are shown in Table 2.

[0131] Table 2 Performance parameters of the inks prepared in Examples 4-6 and Comparative Examples 1-3

[0132] Performance indicators Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Oxygen transmission rate (cc / m²·day) 3.5 2.8 4.2 35.3 13.6 28.7 Water vapor transmission rate (g / m²·day) 2.2 1.9 2.4 22.4 10.3 18.8 Viscosity (Ford cup 4 / s, 25°C) 23 30 18 15 28 20 Fineness (μm) ≤5 ≤5 ≤5 ≤15 ≤25 ≤10 Adhesion strength (%) 98 99 97 82 75 95 VOCs (%) 3 4 3 4 3 52

[0133] As shown in Table 2, the oxygen permeability of Examples 4-6 were 3.5 cc / m²·day, 2.8 cc / m²·day, and 4.2 cc / m²·day, respectively, significantly better than the 35.3 cc / m²·day of Comparative Example 1. The cross-linked polyvinyl alcohol network structure of Examples 4-6 blocked the gas permeation path, and the -NH₂ of the KH-550 modified nanomaterials bonded to the carboxyl groups of the resin, forming a dense barrier. The oxygen permeability of Comparative Example 2 was 13.6 cc / m²·day; the unmodified nanoparticles agglomerated, resulting in a fineness increase to 25 μm, causing discontinuous barrier paths. In Comparative Example 3, the nano-calcium carbonate in the solvent-based ink was randomly distributed, resulting in low barrier efficiency and an oxygen permeability of 28.7 cc / m²·day.

[0134] The water vapor transmission rates in Examples 4-6 were 2.2 g / m²·day, 1.9 g / m²·day, and 2.4 g / m²·day, respectively. The acetalization reaction of polyvinyl alcohol with glutaraldehyde / glyoxal blocked the hydroxyl groups of polyvinyl alcohol, reducing its hydrophilicity; a dense network with crosslinking point spacing ≤2 nm was formed, blocking the pathway of water vapor. Amino-grafted nanoparticles were oriented to extend the diffusion path of water molecules, and -NH₂ groups were bonded to the carboxyl groups of acrylic acid, blocking the interfacial micropores. The high-solids acrylic resin improved the film continuity and reduced pinhole defects; the hydrophobic methyl side chains blocked water permeation. Small molecules of citrate / epoxidized soybean oil filled the gaps at the polyvinyl alcohol-acrylic acid interface and did not contain hydrophilic groups.

[0135] In Comparative Example 1, the pure acrylic resin membrane has a large number of hydrophilic carboxyl groups and no cross-linked structure, with a water vapor transmission rate of 22.4 g / m²·day. In Comparative Example 2, the unmodified nano-SiO2 severely agglomerates, forming rapid water molecule channels ≥100 nm around the agglomerates. The weak interfacial bonding leads to microcracks, resulting in a water vapor transmission rate of 10.3 g / m²·day. In Comparative Example 3, although the solvent-based membrane forms a dense film, the nano-calcium carbonate lacks interfacial modification, resulting in poor compatibility with the resin. Solvent evaporation leaves micropores, leading to a water vapor transmission rate of 18.8 g / m²·day.

[0136] The viscosity of Examples 4-6 is stable at 15-30 s, suitable for high-speed printing. In Comparative Example 2, the unmodified nano-silica agglomerates, resulting in poor leveling. The fineness of Examples 4-6 is less than 5 μm, which is significantly better than that of Comparative Examples 1-3.

[0137] The adhesion strength of Examples 4-6 is greater than 97%, which is significantly higher than that of Comparative Example 2 (75%). Comparative Example 2 has weak interfacial bonding due to the lack of modification of nano-silica.

[0138] Examples 4-6 used water as a solvent and employed citrate ester / epoxidized soybean oil, with VOCs meeting the requirement of ≤30%. In Comparative Example 3, an ester solvent was used, resulting in VOCs increasing to over 50%.

[0139] This invention utilizes cross-linked polyvinyl alcohol to improve water resistance, interfacial bonded nanocomposite materials to improve barrier properties, and high-solids acrylic resin to improve film density. These three components work synergistically to reduce oxygen and moisture permeability.

Claims

1. An aqueous high barrier ink, characterized in that, By weight percentage, comprising the following components: Polyvinyl alcohol emulsion 20~40%, acrylic resin emulsion 10~20%, nanocomposite 5~15%, bio-based plasticizer 3~8%, dispersant 1~3%, wetting agent 0.2~1%, defoaming agent 0.1~0.5%, leveling agent 0.1~0.5%, and the balance is water; Wherein, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol emulsion is 18~23%, and the mass fraction of acrylic resin in the acrylic resin emulsion is 47~52%.

2. The water-based high barrier ink according to claim 1, characterized in that, The nanocomposite is a nanomaterial modified by a silane coupling agent, and the nanomaterial includes nanoclay or nanosilica.

3. The water-based high barrier ink according to claim 1, characterized in that, The bio-based plasticizer includes citrate or epoxy soybean oil.

4. A production method suitable for producing the water-based high-barrier ink according to any one of claims 1 to 3, characterized by, Comprising the following steps: S100, preparation of polyvinyl alcohol emulsion: dissolving polyvinyl alcohol in water, adjusting pH to 2~4; adding crosslinking agent to complete the reaction; adding emulsifier, stirring and emulsifying to obtain polyvinyl alcohol emulsion; S200, preparation of water-based high-barrier ink: mixing the raw materials according to the component ratio of the water-based high-barrier ink of any one of claims 1~3 to obtain the water-based high-barrier ink.

5. The preparation method according to claim 4, characterized in that, In step S100, the crosslinking agent includes glutaraldehyde or glyoxal, and the molar ratio of the crosslinking agent to polyvinyl alcohol is 9~11:

1.

6. The preparation method according to claim 4, characterized in that, In step S100, the emulsifier includes sodium dodecyl sulfate or OP-10, and the emulsifier accounts for 0.5~1% of the total mass of monomers.

7. The preparation method according to claim 4, characterized in that, In step S100, specifically including: dissolving polyvinyl alcohol in water, heating to 80~90℃, stirring to completely dissolve, adjusting pH to 2~4; adding crosslinking agent for 1~2; cooling to 50~60℃, adding emulsifier, stirring and emulsifying to obtain polyvinyl alcohol emulsion.

8. The preparation method according to claim 4, characterized in that, In step S200, the preparation of water-based high-barrier ink includes the following steps: Step 1, add water, dispersant, wetting agent, defoaming agent and leveling agent into the stirring kettle and stir uniformly; Step 2, add nanocomposite and disperse at high speed to fineness≤10μm; Step 3, add modified polyvinyl alcohol emulsion and acrylic resin emulsion and stir uniformly; Step 4, filter to obtain water-based high-barrier ink.

9. The preparation method according to claim 4, characterized in that, The preparation method of nanocomposite includes the following contents: dispersing nanomaterial in water according to solid-liquid ratio 1:1.8~2.1, adding silane coupling agent, and reacting at 60~80℃ for 2~3 hours; filtering, washing and drying to obtain surface-modified nanocomposite.

10. The method of claim 10, wherein, The molar ratio of nanomaterial to silane coupling agent is 18~21:1.

Citation Information

Patent Citations

  • Method for synthesizing ionic polyvinyl butyral latex

    CN101445570A

  • Bright black plasticizing ink

    CN103923518A

  • Heat sublimation transfer printing ink and preparation method thereof

    CN106519798A

  • High-transmittance UV roller coating protective ink and preparation method thereof

    CN114231080A

  • Intaglio printing ink and preparation method thereof

    CN116376356A

Cited By

  • Water-based ink as well as preparation method and use method thereof

    CN121652639A

  • Environment-friendly printing ink

    CN121718214A